1996
DOI: 10.1016/s1078-5884(96)80248-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of Duplex scanning in evaluation of crural and foot arteries in limbs with severe lower limb ischaemia — A prospective comparison with angiography

Abstract: The results demonstrate the feasibility and reliability of Duplex scanning in detecting crural and pedal artery lesions in lower limbs with severe ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…Some study groups (Grassbaugh et al 2003;Karacagil et al 1996;Boström et al 2002;Mazzariol et al 2000) have shown duplex ultrasound to be highly accurate in localizing and grading steno-occlusive disease of the calf arteries and to enable reliable planning of the surgical approach and identification of a potential bypass target below the knee, with bypass patency rates here being similar to those in patients examined by preoperative angiography. The choice of the preoperative imaging modality in patients with popliteal occlusion and involvement of the calf arteries in stage III and IV PAOD depends not only on the expected diagnostic information but also, and importantly, on the examiner's skills and experience with duplex ultrasound, the time available (see Sect.…”
Section: Specific Aspects Of the Examination From The Perspective Of mentioning
confidence: 94%
“…Some study groups (Grassbaugh et al 2003;Karacagil et al 1996;Boström et al 2002;Mazzariol et al 2000) have shown duplex ultrasound to be highly accurate in localizing and grading steno-occlusive disease of the calf arteries and to enable reliable planning of the surgical approach and identification of a potential bypass target below the knee, with bypass patency rates here being similar to those in patients examined by preoperative angiography. The choice of the preoperative imaging modality in patients with popliteal occlusion and involvement of the calf arteries in stage III and IV PAOD depends not only on the expected diagnostic information but also, and importantly, on the examiner's skills and experience with duplex ultrasound, the time available (see Sect.…”
Section: Specific Aspects Of the Examination From The Perspective Of mentioning
confidence: 94%
“…Conventional angiography is used for vascular interventions such as angioplasty or stent application, as well as in the diagnosis of peripheral arterial disease. Doppler US is the only noninvasive technique that does not require contrast enhancement, preparation of the patient before the study, or radiation exposure [1,2]. Doppler US is a good method for screening and follow-up, as well as for the definitive diagnosis of peripheral arterial disease [3-7].…”
Section: Introductionmentioning
confidence: 99%
“…The target artery and its branches are overlaid as a red (a) or blue (b) line on a study done to evaluate the potential of an image overlay system in peripheral vascular surgery. The advantages of US include that it is noninvasive, it does not involve radiation exposure, and it provides hemodynamic information as well as morphological data [9][10][11]. On the other hand, its utility is limited because it requires more time than other imaging modalities and its quality is operator-dependent [6][7][8][9]12].…”
Section: Discussionmentioning
confidence: 99%
“…The depth of the target vessel and its anatomical relationship with the bones are also important factors. For example, the terminal branches of the peroneal artery and the anterior tibial artery within the interosseous membrane and beneath the extensor retinaculum are difficult to assess by US, even in normal limbs [5,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation